MEASUREMENT OF THE PARTIAL WIDTH OF THE Z0 INTO B(B)OVER-BAR FINAL-STATES USING THEIR SEMILEPTONIC DECAYS - Abreu, P; Adam, W; Adye, T; Agasi, E; Alekseev, G; Allen, P; Almehed, S; Alvsvaag, S; Amaldi, U; Anassontzis, E; Andreazza, A; Antilogus, P; et al. (1992)
The spectra of prompt electrons and muons from the semi-leptonic decays of heavy hadrons produced in Z0 decays have been used to measure the coupling of the Z0 to b quarks weighted by the B hadrons mean semi-leptonic branching fraction, giving a value: Mathematical expression. The data has also been used to measure the value of the fragmentation parameter, defined in the context of the LUND PS Model, version 7.2, giving: Mathematical expression. The corresponding value of the mean fraction of the beam energy taken by a B hadron in the fragmentation of a b quark is: Mathematical expression. If the values of Mathematical expression and ΓH are taken from the Standard Model, the following value is obtained for the mean semi-leptonic braching fraction of B hadrons: BRslb=(10.1±0.7)%. Taking the value of Mathematical expression from an independent analysis of DELPHI data based on the use of the boosted sphericity product, a value: BRslb=(10.1±1.3)% is obtained. © 1992 Springer-Verlag.